2020
DOI: 10.13023/jah.0202.07
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Care at Free Episodic Health Care Clinics in Appalachia

Abstract: Background People who live in rural Appalachia experience a wide variety of problems when seeking access to health care. Health care disparities continue to be one of the most complex and prevalent problems, and many barriers exist for impoverished men and women such as a lack of education, complications with health insurance, and personal distrust of healthcare providers. Purpose A critical gap in the literature is the unheard voice of persons in rural underserved area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Because the larger research study aimed to capture patient and provider experiences of health and health care, seven interviewees were practicing or retired healthcare providers (including nurses, physicians, a midwife, and a clinical social worker). Previous health-related qualitative studies in rural communities 11 , 15 17 have shown that a sample size of 14 is sufficient to reach theoretical saturation within the data. 11 , 18 All interviewees self-identified as white and non-Hispanic and ranged in age from 29 to 90 years.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Because the larger research study aimed to capture patient and provider experiences of health and health care, seven interviewees were practicing or retired healthcare providers (including nurses, physicians, a midwife, and a clinical social worker). Previous health-related qualitative studies in rural communities 11 , 15 17 have shown that a sample size of 14 is sufficient to reach theoretical saturation within the data. 11 , 18 All interviewees self-identified as white and non-Hispanic and ranged in age from 29 to 90 years.…”
Section: Methodsmentioning
confidence: 96%
“…Previous health-related qualitative studies in rural communities 11 , 15 17 have shown that a sample size of 14 is sufficient to reach theoretical saturation within the data. 11 , 18 All interviewees self-identified as white and non-Hispanic and ranged in age from 29 to 90 years. There were an equal number of male and female interviewees.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Individuals in the Appalachian region, especially rural Appalachia, face increased contextual stressors linked to disease development and morbidity (Lazar et al, 2020) and demonstrate culturally distinct close family ties. Given the health vulnerability of individuals in the Appalachian region (Cossman et al, 2007;Marshall et al, 2017;Spleen et al, 2014), the tendency toward close family networks (Keefe, 2005), and guided by the BBFM Wood, 1993;Wood et al, 2015), it is important to understand the links between family emotional climate (i.e., marital and family relationship quality) and biobehavioral reactivity and disease activity.…”
Section: The Present Studymentioning
confidence: 99%
“…The limited literature examining the role of nonmarital relationships in adult populations indicates that marital and nonmarital family relationship quality is important for health outcomes. Still, this relationship-health pathway remains understudied in under-resourced populations with increased contextual stressors, including rural populations (Lazar et al, 2020).…”
Section: The Biobehavioral Family Model (Bbfm)mentioning
confidence: 99%